APPLICATION OF KAOLIN-ZEOLITE CERAMIC FILTER MEMBRANE IN RECOVERING WASTE OIL INTO USABLE OIL - Zaky, Muhammad; Putra, Alfian; Rahmawati, Cut Aja (Politeknik Negeri Lhokseumawe, 2025)
Several membrane materials are continuously being developed to produce efficient and environmentally friendly filtration media. This study examines the application of kaolin-zeolite-based ceramic filter membranes in the process of refining used cooking oil into usable oil. The main materials used are kaolin, zeolite, and PVA as a binder. The variations in the kaolin:zeolite composition used are 50%:50%, 60%:40%, 70%:30%, 80%:20%, and 100%:0% with sintering times of 1, 2, and 3 hours at a temperature of 1000°C. Membrane characterization includes density, porosity, flux, morphology tests using a Scanning Electron Microscope (SEM), as well as the removal of Free Fatty Acids (FFA) in used cooking oil. The results showed that the composition of 50% kaolin and 50% zeolite with a sintering time of 3 hours produced the best performance with a density of 1.32 g/cm³, porosity of 56.00%, flux of 143.93 L/m².hour, and the removal capacity of ALB up to 70.6%, reducing the ALB content from 4.56% to 1.34% according to SNI standards. SEM analysis showed a macroporous structure (0.57–3.02 µm) that supports filtration, while the adsorptive properties of zeolite play a role in reducing polar compounds. These results prove that kaolin-zeolite ceramic membranes have the potential as an alternative technology in used cooking oil recovery. Keywords: Ceramic Membrane, Kaolin, Zeolite, Sintering, Flux, Free Fatty Acid, SEM.